Financing Sustainable Development : Ideas for Action 2017 - Mohieldin, Mahmoud (World Bank, Washington, DC, 2017)
This report presents the results of the 2017 Ideas for Action (I4A) initiative, a youth competition on financing for development that was jointly organized by the World Bank Group and the Zicklin Center for Business Ethics Research at the Wharton School of the University of Pennsylvania. This is the third year of the competition, and the 2017 winners were selected from among 743 proposals from 118 countries. Today’s youth have the most at stake in achieving the 2030 Agenda for Sustainable Development, and its associated Sustainable Development Goals (SDGs). The world’s youth will implement this global agenda, contributing their unique solutions and shaping their future and ours. The I4A competition encourages young people from around the world to develop and share their ideas for innovative approaches, through the smart use of technology, as well as financing solutions, to solve development challenges. The winners were selected through a vigorous three-stage selection process evaluating the creativity, significance, feasibility, and clarity of the proposals.